If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 86 + (6x + -2) = 180 Reorder the terms: 86 + (-2 + 6x) = 180 Remove parenthesis around (-2 + 6x) 86 + -2 + 6x = 180 Combine like terms: 86 + -2 = 84 84 + 6x = 180 Solving 84 + 6x = 180 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-84' to each side of the equation. 84 + -84 + 6x = 180 + -84 Combine like terms: 84 + -84 = 0 0 + 6x = 180 + -84 6x = 180 + -84 Combine like terms: 180 + -84 = 96 6x = 96 Divide each side by '6'. x = 16 Simplifying x = 16
| 12+[x+3]=10 | | (7x+2)(-x-9)= | | (1-2i)(1+3i)= | | T^2+2t-9=t+3 | | 8t^2-36t+28=0 | | Y-40=26 | | (2/9)(6/5) | | 7x-6=-46 | | 9/4.4=2.5 | | 1000*Y=9.3616 | | 64m+5= | | 9.3=0.31n | | 6x+3-11=4 | | 8(4-x)=7+2x | | 4(t-2)+11-4=2t+3 | | 7/24-1/3 | | 4+14m-1=8m+75-3m | | 9x+3x=5x+10 | | -2w+7=3x-3 | | 12-58= | | 27+1x=23 | | 5x-(12-2x)=3x | | 7.3x-1.8=20.1 | | -b=72 | | -1x+28=18 | | 10x+180=(x+10)(x+4) | | 66y=132 | | -26+5x=24 | | 21=5m+6+5 | | 12x-2=150 | | 5h-7=12(h+1) | | 72+-5x=27 |